Rare fungus, Mortierella capitata, promotes crop growth by stimulating primary metabolisms related genes and reshaping rhizosphere bacterial community. (December 2020) - Li, Fang; Zhang, Shuiqing; Wang, Yi; Li, Yue; Li, Peipei; Chen, Lin; Jie, Xiaolei; Hu, Desheng; Feng, Biao; Yue, Ke; Han, Yanlai
Abstract: Rhizosphere and endosphere microorganisms are recognized as an extended plant genome. Changes in rhizosphere and endosphere microbial community structure are closely linked to plant nutrition uptake, development and immunity. Mortierella is a saprophytic oleaginous fungus, with various agricultural benefits, which have triggered interest in recent years. Here, we conducted Mortierella capitata inoculation experiments in a climate chamber. M. capitata inoculation increased biomass, chlorophyll and gibberellic acid content in maize. The concentration of available soil phosphorus was also increased, while O2 concentration and soil density decreased. Further, the prokaryotic and eukaryotic microbial structure was evaluated by MiSeq sequencing. M. capitata inoculants increased rhizosphere bacterial diversity and significantly altered rhizosphere bacterial community composition. Yet, the influence of M. capitata on fungal community structure was not significant according to ANOSIM analysis. RNA-seq was used to ascertain differentially expressed genes (DEGs) in maize roots following M. capitata inoculation. Genes encoding chitinase, peroxidase, lipid transfer protein, sugars exported transporter, and various transcription factor proteins were significantly up-regulated. All the DEGs, soil and plant basic properties were used to construct a co-occurrence network for modularity analysis. The whole network was divided into five modules based on Louvain algorithm, including organic substances metabolism and hormone regulation, nucleobases metabolism, stimulus response, primary metabolism and an unknown module. The stimulus response module showed the closest correlation with biomass, soil oxygen, and M. capitata, while genes in the primary metabolism module were closely associated with plant gibberellic acid and available soil phosphorus. Our results highlight that the rare fungus M. capitata can promote crop growth directly by altering the root gene expression levels, and indirectly via interaction with indigenous rhizosphere bacteria. Highlights: Rare fungal Mortierella capitata increased available phosphorus concentration and Glomeraceae abundance in rhizosphere soils. Mortierella capitata inoculation reshaped rhizosphere bacterial community structure and increased its α diversity. Mortierella capitata up-regulated maize genes involved in sugars export transport and lipids import transport. A putative model of Mortierella capitata enhancing maize growth was proposed.